Diseño de un cuadro de mando integral como herramienta de gestión de clientes para la agencia Mibanco – sucursal Chepén - Solis Gil, Eyner Loreto (2019)
The present of professional sufficiency entitled "Design of an Integral Control Panel as a Client Management Tool for the MiBanco Agency - Chepén Branch", is proposed to improve the management of Clients, in order to guide and develop pre-established objectives, and to interweave In an efficient manner, the activities and tasks for the achievement of the mission, to the financial entities, correspond to the growth and increase in terms of attracting customers, which consequently will generate great benefits in said entity. This work presents the design of a Balanced Scorecard for the financial entity MiBanco - Chepén Branch, where, in the first place, the problem is determined, the objectives and their justification are stated, the theoretical and legal basis is disclosed. supports the design model in question: the perspectives contained in the balanced scorecard, the dashboard, the basis of how the financial system is organized, banking and non-banking system; secondly, the design of the balanced scorecard, the strategic map (cause-effect matrix) for the financial institution under study will be taken into account; the implementation has been developed with the methodology of the Kaplan and Norton model, incorporating some experiences obtained by the author; thirdly, some conclusions and recommendations are presented in this investigation and, finally, the suggestion and methods for the training of systems engineers are presented.